1987
DOI: 10.1203/00006450-198710000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Renal β-Adrenoceptor-Mediated Vasodilation in Sheep: Comparison between Endogenous Catecholamines

Abstract: ABSTRACT. The renal hemodynamic response to renal arterial infusions of norepinephrine was compared to epinephrine infusions during renal a-adrenoceptor blockade in chronically instrumented and unanesthetized fetal (127-141 days gestation; term 145 days), newborn (6-10 days old), and nonpregnant adult sheep. Infusions of either catecholamines produced renal vasodilation which was of greater magnitude in fetal compared to newborn and adult sheep. Maximal increases in renal blood flow velocity during norepinephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
2
4
1
Order By: Relevance
“…This response could be inhibited by ICI 1 1835 1, a specific P2-adrenoceptor antagonist (23), supporting the concept that vascular P2-adrenoceptors are functional early during renal maturation. These results are consistent with our previous study demonstrating enhanced renal P-adrenergic response to renal nerve stimulation (24) and infused norepinephrine (9) in fetal sheep and provide evidence of an age-dependent P-adrenergic renal vasodilator mechanism during development in sheep. Furthermore, one may speculate that the ontogeny of renal vascular P-adrenoceptor-mediated responses are similar whether adrenoceptor stimulation occurs with neurotransmitter release or by activation of extrajunctional adrenoceptors via circulating catecholamines (25).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This response could be inhibited by ICI 1 1835 1, a specific P2-adrenoceptor antagonist (23), supporting the concept that vascular P2-adrenoceptors are functional early during renal maturation. These results are consistent with our previous study demonstrating enhanced renal P-adrenergic response to renal nerve stimulation (24) and infused norepinephrine (9) in fetal sheep and provide evidence of an age-dependent P-adrenergic renal vasodilator mechanism during development in sheep. Furthermore, one may speculate that the ontogeny of renal vascular P-adrenoceptor-mediated responses are similar whether adrenoceptor stimulation occurs with neurotransmitter release or by activation of extrajunctional adrenoceptors via circulating catecholamines (25).…”
Section: Discussionsupporting
confidence: 82%
“…Comparisons of dose response curves between fetal, newborn, and adult sheep were performed by simultaneous analysis of physiological dose-response curves as described by DeLean et al (17) and previously used by us (8,9). These comparisons were done by using the ALLFIT program adapted for an Apple computer by Martin H. Teicher, Department of Psychiatry, Harvard Medical School.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, these results differ from previous studies (27)(28)(29) demonstrating that the renal vasodilatory response to Padrenoceptor stimulation is greater in fetal sheep than in newborn lambs. A recent study (30) using forskolin, a drug known to activate adenylate cyclase directly (3 I), has suggested that the greater P-adrenoceptor-mediated renal vasodilation in fetal sheep may be at the receptor-hormone level.…”
Section: Discussioncontrasting
confidence: 56%
“…At high ICP /J-adrenergic blockade in dogs unmasks a large a-adrenergic vasoconstriction, 910 the pattern of which closely resembles that in fetal lambs. However, a recent study showing that /3-adrenergic vasodilation in the kidney is welldeveloped in near-term fetal sheep 22 makes underdevelopment of /3-adrenoceptors an unlikely explanation.…”
Section: Comparison With Adult Cushing Responsementioning
confidence: 97%